A Community Collaborative to Develop Consensus Guidelines to Standardize Out-of-Hospital Maintenance Care of Central Venous Catheters. Issue 2 (March 2015) - Nailon, Regina; Rupp, Mark E.
Abstract : Central venous catheter (CVC) maintenance is integral to preventing complications and improving outcomes. This process is made more challenging when patients transition from hospital to home care or to an outpatient infusion setting, because different CVC maintenance practices and care parameters confuse patients and care providers alike. Through collaboration and consensus building, a group of metropolitan home health and home infusion agencies developed a standardized approach to CVC maintenance care. This article discusses the multiagency collaborative and resulting guideline and other educational materials that better enable providers, patients, and families to maintain CVC integrity and achieve optimal outcomes.